The biomedical application and corrosion properties of implanted materials with protective coatings - Zykova, A.V.; Luk’yanchenko, V.V.; Safonov, V.I. (Вопросы атомной науки и техники, 2005)
For purposes of orthopedic and trauma surgery operations various stems, spokes, screws, pins made of pure metal and alloys are widely applied. As a result of metal materials using the problems of the patient organism protection from deleterious effects of metallogenic and electrochemical reactions, metal toxicosis – complications, connected with metal ion effect on organism, arise. The present study is devoted to realization of the comparative analysis of corrosion properties of modern implanted materials and coatings in simulated body fluid and their long-term behaviour in animate organism.